Digital Economy and Green Growth Opportunities and Challenges for Urban and Regional Ecosystems - Mavri, Maria; Ikouta Mazza, Patricia; Karasavvoglou, Anastasios; Polychronidou, Persefoni (Contributions to Economics, 2024)
X, 188 p. 40 illus., 35 illus. in color.